The first two CABG Surgeries in Nepal - Pokhrel, D P; Tuladhar, Subarna (Nepalese Heart Journal, 2000)
The cardiothoracic and vascular surgery unit of Bir Hospital made a landmark in the history of Nepalese surgery by performing two open heart coronary artery bypass graft surgeries under the leadership of Dr. D. P. Pokharel and an entirely Nepali team on 2057/3/4 an 2057/3/7.